SOME LEGAL ISSUES OF THE MANAGEMENT OF NON-GOVERNMENTAL ORGANIZATIONS - Bekzod Narimanov (Scholars Digest Publishing, 2023)
This article is analyzed on the basis of regulatory legal acts on certain legal issues related to the management of non-profit organizations. An analysis of the norms provided for by the legislation on the rights of non-governmental non-profit organizations to own, use and dispose of property was also carried out. At the same time, opinions and reflections were expressed on the role and tasks of the third sector in the current life of society and the state. At the same time, non-profit organizations expressed opinions on cases of non-governmental activities. In addition, the legislation of foreign states provides norms for non-governmental non-profit organizations on the rights to own, use and dispose of property. At the same time, the article presents problematic situations in several practices to solve the alleged problem.
Keywords: ownership of property, its use and disposal, financial transactions, minimizing the risk of abuse, property management.